2018
DOI: 10.1038/s41598-018-33262-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher species richness enhances yield stability in intensively managed grasslands with experimental disturbance

Abstract: Climate models predict increased frequency and severity of drought events. At an Irish and Swiss site, experimental summer droughts were applied over two successive years to grassland plots sown with one, two or four grassland species with contrasting functional traits. Mean yield and plot-to-plot variance of yield were measured across harvests during drought and after a subsequent post-drought recovery period. At both sites, there was a positive relationship between species richness and yield. Under rainfed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 41 publications
6
66
2
1
Order By: Relevance
“…Overall, mixtures were slightly more productive than sole crops but no difference was observed on yield stability. While most studies investigating the influence of species diversity showed a positive correlation between diversity and biomass production or stability (Haughey et al, 2018;Hector et al, 2010;Isbell et al, 2009;Nyfeler et al, 2009), we did not observe that increasing species diversity in mixtures results in higher and more stable biomass yield. Two plausible explanations could be the varied influence of species identity according to diversity level, and the influence of the growing conditions.…”
Section: Effect Of Species Diversity and Identity On Biomass Producticontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall, mixtures were slightly more productive than sole crops but no difference was observed on yield stability. While most studies investigating the influence of species diversity showed a positive correlation between diversity and biomass production or stability (Haughey et al, 2018;Hector et al, 2010;Isbell et al, 2009;Nyfeler et al, 2009), we did not observe that increasing species diversity in mixtures results in higher and more stable biomass yield. Two plausible explanations could be the varied influence of species identity according to diversity level, and the influence of the growing conditions.…”
Section: Effect Of Species Diversity and Identity On Biomass Producticontrasting
confidence: 99%
“…Several studies conducted in natural ecosystems (Hooper et al, 2005) and intercropping (e.g. Andersen et al, 2004;Bedoussac and Justes, 2010;Hauggaard-Nielsen et al, 2006) showed that the performance of a mixture can exceed the average of the individual to higher stability in biomass production (Haughey et al, 2018;Tilman et al, 2006;Yachi and Loreau, 1999). It has been shown for example that, for a broad range of extreme climate events, high-diversity communities (16-32 species) had higher productivity stability, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, pathways to exploit the positive plant diversity effects over longer periods could include increasing livestock diversity to promote plant diversity 60 , maintaining and promoting species-diverse hay meadows, e.g., Arrhenatheretum elatioris, with two to three cuts and low to moderate fertilization levels 61 , and seeding of plant diverse mixtures containing complementary species and legumes. Such plant diverse mixtures can also be helpful in dealing with droughts [62][63][64] , which are becoming more severe and frequent under changing climatic conditions 65 . Maintaining and reestablishing plant diverse grasslands could provide a win-win situation as it enables a sustainable increase in quality-adjusted yield and revenues, while at the same time it supports other important ecosystem services and functions.…”
Section: Management Effectmentioning
confidence: 99%
“…It can be one measure to develop more sustainable production systems, develop value-chains for minor crops (Meynard et al 2018) and contribute to socio-economic benefits (Feliciano 2019). Crop diversification practices can include higher crop diversity (Renard and Tilman 2019), more diverse crop rotations (Reckling et al 2016), mixed cropping (Bedoussac et al 2015;Malézieux et al 2009), cultivation of grain legumes in otherwise cereal dominated systems (Watson et al 2017), perennial leys or grassland (Haughey et al 2018;Phelan et al 2015;Weißhuhn et al 2017) and regionally adapted varieties or variety mixtures (Yang et al 2019;Vijaya et al 2019). Crop diversification and/or additional diversification measures like variation of seeding time or changing cropping patterns have the potential to lead to higher and more stable yields, increase profitability and lead to greater resilience of agro-ecosystems in the long term (Rosa-Schleich et al 2019;Meynard et al 2018;Liu et al 2019;Raseduzzaman and Jensen 2017;Renard and Tilman 2019;Urruty et al 2016).…”
Section: Introductionmentioning
confidence: 99%